The role of systemic risk spillovers in the transmission of Euro area monetary policy - Alexandros Skouralis (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2021)
This paper empirically investigates the transmission of systemic risk across the Euro Area by employing a Global VAR model. We find that a union aggregate systemic risk shock results in a sharp decline in output, with two thirds of the response to be attributed to cross-country spillovers. The results indicate that peripheral economies have a disproportionate importance in spreading systemic risk compared to core countries. Then, we incorporate high-frequency monetary surprises into the model and we find evidence of the risk-taking channel of monetary policy. However, the relationship is reversed in the period of the ZLB, when expansionary shocks mitigate systemic risk. Cross-country spillovers account for a significant fraction (17.4%) of systemic risk responses' variation. We also show that near term guidance reduces systemic risk, whereas the initiation of the QE program has the opposite effect. Finally, the effectiveness of monetary policy exhibits significant asymmetries, with core countries driving the union response.
Keywords: C32; E44; F36; F45; 330; Systemic risk; Global VAR model; Eurozone